Blood Cu/Zn Ratio in Children of School Age, Living in Malaria Endemic Area in Abidjan (Côte D’ivoire) - M’boh, Gervais Melaine; Boyvin, Lydie; Beourou, Sylvain; Djaman, Allico Joseph (International Journal of Child Health and Nutrition, 2013)
Background: Food intake contains various nutrients which the loss or destruction are exogenous factors of oxidative damages in our body, aggravated by infectious diseases. Blood ratio Cu/Zn is an indicator about the pool of defenses anti oxidizing to measure damage oxidative. The present study aimed to investigate the blood ratio Cu/Zn an indicator of pool of oxidative stress and eating risk factors in children school age, living in malaria endemic area. Methods: A total of 113 participants, aged 5-14 years with a mean age about 9.5 ±2 were submitted to the study. Malaria diagnosis was based on clinical grounds as the feverish condition (axillary temperature ≥ 37°C) and confirmed by laboratory test. A survey was conducted to screen children eating habits, and conjointly blood ratio Cu/Zn analyzed by atomic absorption spectrometry. Results: We have noted a high value of the Cu/Zn ratio in malarial children, as compared to controls (p < 0.001). This ratio in both groups was highest compared to the normal values (< 1), and showed an acute value in course of parasitemia. Elsewhere, it was identified eating risk factors in all children. Conclusion: Children of school age in high endemic zone of malaria in Côte d’Ivoire are exposed to the damage of stress oxidative. Thus, eating habits and their interaction with the parasite growth should be analyzed, to correct the states of stress by monitoring down the ratio copper/zinc.